Penerapan Kaidah Munâsabat Ayât dalam Tafsir (Studi Analisis Kaidah Munâsabat Khalîd Bin Utsmân Al-Sabit) - Sartika, Ela (Sekolah Tinggi Ilmu Ushuluddin Wadi Mubarak Bogor, 2022)
The science of munâsabah in ‘ulumul Qur’an becomes one of the tools in analyzing and understanding the Qur’an until it enters the level of interpretation. The views of scholars regarding the science of munâsabah do not all accept the existence of this knowlagde as Imam Asy-Syaukani. Imam Asy-Syaukani very strict is not recognizing and believing in the existence of munâsabah science. However, many commentators have actually succeeded in making a work in which it focuses on the study of munâsabah such as Imam As-Suyuti. This Study aims to find out the rules about the science of munâsabah verses which contain the nature of Asmaul Husna which is closely related to law, by focusing on several classical and contemporary commentaries. research studies in classical and contemporary commentaries. This study also uses of analytical description method. By analyzing the rules of munâsabah verses explained by Khalid bin ‘Ustman al-Sabit to several classical and contemporary commentary books that represent it, it can be concluded that some of these interpretation use the verse munâsabah rules offered by Khalid Ibn ‘Ustman Al-Sabit even though they are explained in detail or general.